Analysis effect of winding on radiation-electromagnetic field on the tesla coil. Issue 1 (April 2021) - Mulhayatiah, D; Setiawan, Y; Rizaldi, M F; Siregar, H S; Suherdiana, D; Nurdini, S D
Abstract: Utilization of modern technology has been widely felt by the public as well as utilizing wireless charging technology on android phones. The charging, of course, uses the concept of Tesla coil, namely the transfer of electricity without wires. The Tesla coil can emit electromagnetic radiation which depends on its input. This study aims to design a miniature tesla coil as a magnetic inductor. In this design, measuring electromagnetic radiation with a coil diameter of 0.3 mm, 0.4 mm and 0.5 mm with the same number of turns is 500 turns. The method used is an experimental method using determinants such as the diameter of the coil, the height of the measurement of electromagnetic radiation, and the distance measurement of electromagnetic radiation. Experiments carried out varying independent variables including diameter of the coil, measurement distance, height and number of turns as a constant quantity. The measurement uses the electromagnetic radiation detector DT-1130 to measure the electromagnetic radiation at several heights of the Tesla coil. The results showed that electromagnetic radiation which has the highest value is at the top or at the end of the coil for the position near the primary coil obtained the lowest electromagnetic radiation results among the three measurements, whereas for distance researchers get the result that the further measurement between the electromagnetic sensor and the Tesla coil electromagnetic radiation is getting weaker. At a winding diameter of 0.3 mm which produces the smallest radiation but when brought closer to the Neon lamp the light intensity of the Neon lamp is brighter compared to the diameter of the winding 0.5 mm which has the most radiation.